High performance tandem organic solar cells via a strongly infrared-absorbing narrow bandgap acceptor - Jia, Zhenrong; Qin, Shucheng; Meng, Lei; Ma, Qing; Angunawela, Indunil; Zhang, Jinyuan; Li, Xiaojun; He, Yakun; Lai, Wenbin; Li, Ning; Ade, Harald; Brabec, Christoph; et al. (Nature Communications, 2021)
Tandem organic solar cells are based on the device structure monolithically connecting two solar cells to broaden overall absorption spectrum and utilize the photon energy more efficiently. Herein, we demonstrate a simple strategy of inserting a double bond between the central core and end groups of the small molecule acceptor Y6 to extend its conjugation length and absorption range. As a result, a new narrow bandgap acceptor BTPV-4F was synthesized with an optical bandgap of 1.21 eV. The single-junction devices based on BTPV-4F as acceptor achieved a power conversion efficiency of over 13.4% with a high short-circuit current density of 28.9 mA cm−2. With adopting BTPV-4F as the rear cell acceptor material, the resulting tandem devices reached a high power conversion efficiency of over 16.4% with good photostability. The results indicate that BTPV-4F is an efficient infrared-absorbing narrow bandgap acceptor and has great potential to be applied into tandem organic solar cells.
CRIS-Team Scopus Importer:2021-01-15